Improving mathematics learning outcomes of students in the matriculation class of Santa Maria Senior High School Yogyakarta through tutoring activities - Krisnamurti, Cyrenia Novella (Edumaspul: Jurnal Pendidikan, 2025)
This research is motivated by the suboptimal mathematics learning outcomes of students, as seen from the Mid-Semester Assessment and daily assessments on previous material, specifically relations. This study aims to improve the mathematics learning outcomes of students using the Problem-Based Learning (PBL) model in class X students participating in tutoring activities at a senior high school who reside in a dormitory. This research is a classroom action research (CAR) study with two cycles. The CAR design follows the Kemmis and McTaggart model, which consists of four stages: planning, implementation, observation, and reflection. The research subjects were 32 class X students participating in tutoring activities at a senior high school who reside in a dormitory. Data collection instruments included learning outcome tests and observation sheets on the implementation of learning. Data analysis was conducted using descriptive analysis. The success criterion for this research was that more than 78% of students achieved the Minimum Completeness Criteria (KKM) of 75. The results showed an improvement in mathematics learning outcomes using the PBL model. In the initial condition, only 50% of students met the KKM with an average score of 62.25. In cycle I, 65.63% of students met the KKM with an average score of 70.61, and in cycle II, 84.39% of students met the KKM with an average score of 86.67. Therefore, it can be concluded that the Problem-Based Learning (PBL) model can improve the mathematics learning outcomes of class X students participating in tutoring activities at a senior high school who reside in a dormitory.